The Effect of Expressive Writing on the Experiences of Head and Neck Cancer Patients Undergoing Radiotherapy: A Randomized Controlled Trial - Jiayuan Li; Zhuoran Gao; Siyu Li; Xia Zhong (Cancer Medicine)
ABSTRACT Background Expressive writing (EW) has emerged as an innovative strategy for improving mood and quality of life. Nevertheless, insufficient research has been conducted on the impact of offering EW to patients with HNC. Therefore, the purpose of this study was to investigate the effects of two forms of EW on anxiety, depression, nutrition, and sleep quality in HNC patients undergoing radiotherapy. Methods We conducted a single‐blind, pretest, posttest, three‐group randomized controlled trial. A total of 147 patients with HNC were randomly assigned to a benefit‐finding writing group, neutral writing group, or control group. The intervention group patients performed EW during radiotherapy, with each writing session lasting 20 min, once a week for 4 consecutive weeks. Patient anxiety, depression, nutritional status, and sleep quality were measured at baseline (T0) and at the end of radiotherapy (T1). Results After 4 weeks of intervention, patients in the BF and NW groups experienced improvements in anxiety, depression, and sleep (p < 0.05) compared with those in the CG group, but the intervention did not significantly affect patients' nutritional status (p > 0.05). Compared with those in the CG, anxiety in the BF and NW groups slowed down the trend of increasing anxiety, and repeated measures analysis revealed a significant group × time interaction (p = 0.017, F = 4.205, η2 = 0.059). Compared with those in the CG, the depression levels in the BF and NW groups were lower than those at baseline, and repeated measurement analysis revealed that the interaction effect between group × time was significant (p = 0.000, F = 16.262, η2 = 0.194). The sleep quality in the CG progressively worsened from T0 to T1 (p < 0.01), whereas in the BF, it progressively improved (p < 0.01). Conclusions This study provides preliminary evidence that two forms of EW are effective in alleviating anxiety and depression and improving sleep in patients with HNC but are not effective in improving their nutritional status. Trial Registration: ChiCTR2400084964